SWOT Analysis As A Determiner Of Marketing Strategy At b Hotel Bali & Spa Denpasar - Ni Putu Sri Prajayanti; I M Sudana; I G M Karma (Jurusan Akuntansi Politeknik Negeri Bali, 2021)
This research aims to determine the marketing strategy that must be taken from the results of the SWOT analysis at the b Hotel Bali & Spa Denpasar. This study uses primary data sources and secondary data sources with data collection methods through interviews, observation and questionnaires. The analysis technique used is a qualitative descriptive analysis technique, namely the SWOT analysis technique which explains, first, the data collection stage at the Bali Hotel & Spa Denpasar regarding the identification of internal and external factors in the form of strengths, weaknesses, opportunities, and threats, the second is the analysis stage, and third namely the stage of decision making to determine the strategy to be taken by the company. The research results from the SWOT analysis show that the company is in quadrant I, where it shows a problem regarding for the strength to see opportunities where the strategy taken is the SO strategy used to be applied in developing strategies that can be suggested at management b Hotel Bali & Spa Denpasar, to can improve the progress of the hotel going forward.